KONSEP MASHLAHAH DALAM KONSUMSI - Atika, Jumi (Institut Agama Islam Negeri Padngsidimpuan, 2016)
AbstractIn economic theory one's satisfaction in consuming a product called utility or use value. If the satisfaction of an object is higher, the higher the point value. whereas if the satisfaction of a good getting lower, the lower the value of the point. whereas if the satisfaction of a good getting lower, the lower the value of the point. Satisfaction in conventional terminology meant the fulfillment of physical needs, but consume a product before it reaches the maximum satisfaction is the principle taught Rasullullah consumption, such as eating before getting hungry and stopped before full due to the additional value that will be obtained will decrease if the person continues to consume. In the end, the additional use value will be negative when consumption of the goods continue to be added. So in this paper will be discussed on consumption in Islam, and mashlahah in consumption itself.Keywords : Consumption, Utility, Maslahah